Formal techniques for safety-critical systems : 6th International Workshop, FTSCS 2018, Gold Coast, Australia, November 16, 2018, Revised selected papers /: 6th International Workshop, FTSCS 2018, Gold Coast, Australia, November 16, 2018, Revised selected papers. (2019) - Unknown
No abstract available